Penerapan Terapi Spiritual Berzikir Terhadap Penurunan Emosi Penderita Skizoprenia Melalui Aplikasi Model Betty Neuman Di Puskesmas Simpang Nangka Kabupaten Rejang Lebong Tahun 2025 - Rasyid Akbar; Tita Septi Handayani (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to determine the effect of applying spiritual therapy through zikr on reducing emotional disturbances among patients with schizophrenia using the Betty Neuman Model at Simpang Nangka Community Health Center, Rejang Lebong Regency, in 2025. Schizophrenia is a chronic mental disorder characterized by emotional instability, requiring appropriate nursing interventions to manage patients’ responses to stressors. This research employed a quantitative approach with a quasi-experimental design, specifically a one group pre-test and post-test design. The subjects were schizophrenic patients experiencing emotional disturbances. The intervention consisted of structured zikr therapy based on Neuman’s system model. The findings revealed a significant decrease in emotional levels after the implementation of spiritual therapy. In conclusion, zikr therapy is effective in reducing emotional instability among patients with schizophrenia and can serve as a complementary spiritual-based nursing intervention.